PENGEMBANGAN SISTEM INFORMASI MONITORING TUGAS AKHIR (MONITA) JURUSAN ILMU KOMPUTER FAKULTAS MATEMATIKA DAN ILMU PENGETAHUAN ALAM UNIVERSITAS LAMPUNG - Dimas Aji Sukma; Anie Rose Irawati; Yunda Heningtyas; Didik Kurniawan (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2020)
The 2016 Academic Regulations of University of Lampung article 48 stated that; students are obligated to finish their thesis to be avowed as a graduate of a certain bachelor degree. In the Computer Science Department, theses are managed by the thesis coordinator. Thesis coordinator has several tasks, including monitoring the thesis progress of each student. However, in practice, the monitoring process can not be performed easily. Therefore, a thesis monitoring information system is expected to support the thesis coordinator and thesis supervisors in the Computer Science Department on conducting thesis monitoring, as well as accommodating students in terms of administration ease. This research has successfully generated a Thesis Monitoring Information System developed according to the user requirements, by implementing PHP, MySQL, and Nexmo API.